Berberine Ameliorates Inflammation in Acute Lung Injury via NF-κB/Nlrp3 Signaling Pathway - Chen, Jiyu; Huang, Yanli; Bian, Xiaohong; He, Yan (Frontiers in Nutrition, 2022)
Inflammatory response is the key pathophysiological character of acute lung injury (ALI). Berberine (BBR), a natural quaternary ammonium alkaloid, plays a functional role of anti-inflammation both in vitro and in vivo. However, the underlying mechanism between BBR and ALI has not been clearly expounded. Here, we found that BBR improved the permeability of pulmonary and repressed the inflammatory factors in LPS-induced ALI model. In addition, we demonstrated that BBR could suppress the expression of phosphorylated NF-κB and further restrain the downstream gene of Nlrp3. Moreover, we also revealed that BBR could directly interact with Nlrp3 protein. After knocked down of Nlrp3 by using siRNA, the protective role of BBR was abrogated in vitro. The expression of IL-1β and IL-18 was downregulated by BBR via the two signaling pathway. Notably, in Nlrp3 deficient mice, the protective effect of BBR was abolished. These findings demonstrate that BBR has a depressant effect on inflammatory response caused by LPS via regulating the expression of Nlrp3, providing a potential therapeutic strategy in ALI.